Rechargeable magnesium battery composite electrolyte and preparation method and application thereof
By introducing sulfonimide and phosphate additives into the electrolyte solution of magnesium battery, the conductive interface between the electrolyte structure and the surface of magnesium metal is solved, and the problems of slow diffusion kinetics of magnesium metal and poor compatibility of electrolyte in magnesium batteries are solved. , achieving efficient magnesium battery cycle stability and electrochemical performance.
Patent Information
- Application Number
- CN202411652436.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-14
AI Technical Summary
In the prior art, magnesium batteries lack suitable positive electrode materials and electrolytes, resulting in slow diffusion kinetics of magnesium metal during electrochemical cycles, making it difficult to achieve reversible embedding/detachment, and the electrolyte has poor surface compatibility with magnesium metal, which is easy to be easily. A passivation layer is formed, hindering the transmission of Mg2+.
By introducing sulfonimide additives (such as lithium bistrifluoromethanesulfonimide) and phosphate additives (such as trimethyl phosphate or triethyl phosphate) into the electrolyte, the solvation structure of the electrolyte is regulated. A stable electrode/electrolyte interface is formed to improve ionic conductivity, and a phosphorus-rich magnesium ion conductive interface film is formed on the magnesium metal surface to enhance the transmission ability of Mg2+.
Reversible electrochemical cycle of magnesium metal under high current density is achieved, which significantly improves the cycle stability and electrochemical performance of the battery, reduces the overpotential of dissolution/deposition of magnesium negative electrode, and improves the reversibility of magnesium deposition.
Smart Images

Figure CN119447446A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of rechargeable magnesium batteries, and in particular to a composite electrolyte for a rechargeable magnesium battery and a preparation method and application thereof. Background Art
[0002] Magnesium metal secondary batteries have attracted increasing attention due to their abundant resources, high theoretical specific capacity and high safety. Magnesium metal is abundant in reserves (the eighth most abundant element in the earth's crust) and its price is less than 1 / 30 of that of lithium metal, which makes magnesium batteries have obvious cost advantages. Compared with lithium metal (2046mAh cm -3 ) compared to magnesium metal, the volumetric capacity is as high as 3833 mAh cm -3 ; and it has a low standard hydrogen potential of -2.37V (vs SHE), and its energy density is considerable when matched with a suitable positive electrode material. More importantly, compared with metallic lithium, metallic magnesium is not easy to form dendrites during the electrochemical cycle, which further improves the safety of the battery. In addition, since the chemical properties of metallic magnesium itself are inactive and can exist stably in the air, it is easy to operate stably when used as a negative electrode of the battery. On the whole, magnesium batteries, with their unique advantages, are expected to occupy a place in future high-energy-density energy storage systems.
[0003] Although magnesium metal has potential advantages in cost and capacity, the lack of suitable cathode materials and electrolytes has greatly restricted the development of magnesium batteries. 2+ (0.086nm) and Li + (0.09nm) is similar in ionic radius, but due to the 2+ It has two positive charges, and its charge density is much greater than that of Li + The polarization effect and solvation effect are much greater than that of Li + , resulting in Mg 2+ The diffusion kinetics in solid phase materials are slow, so it is difficult to find suitable materials that can achieve reversible insertion / extraction of Mg 2+ The electrolyte is a key component for magnesium batteries to achieve reversible electrochemical reactions and greatly affects the charge and discharge performance of the battery. For example, the electrochemical window of the electrolyte determines whether side reactions between the electrolyte and the electrode will occur, leading to the formation of a passivation layer; the magnesium ion conductivity of the electrolyte and the electrode / electrolyte interface is also an important factor in the polarization of the battery during the cycle. However, magnesium metal has poor compatibility with most electrolytes. The electrolyte will undergo parasitic side reactions on the surface of magnesium metal, forming a dense passivation layer that hinders Mg from reacting with electrolyte. 2+ Therefore, the development of a new electrolyte with high ionic conductivity and high magnesium metal dissolution / deposition efficiency is of great significance for rechargeable magnesium-ion batteries. Summary of the invention
[0004] Purpose of the invention: In order to solve the problems existing in the prior art, the present invention provides a rechargeable magnesium battery composite electrolyte. By introducing sulfonyl imide additives, the electrolyte solvation structure can be effectively regulated to form a stable electrode / electrolyte interface and improve ionic conductivity, thereby achieving reversible electrochemical cycling of magnesium metal at high current density. In addition, by introducing phosphate additives, a phosphorus-rich magnesium ion conductive interface film is formed on the surface of magnesium metal, which enhances the conductivity of Mg. 2+ The invention also provides a method for preparing and applying the composite electrolyte for a rechargeable magnesium battery, and improves the transfer capacity of magnesium, reduces the overpotential of magnesium negative electrode dissolution / deposition, and improves the reversibility of magnesium deposition. These improvements significantly improve the cycle stability of the battery and show excellent electrochemical performance.
[0005] Technical solution: The rechargeable magnesium battery composite electrolyte provided by the present invention includes an organic ether solvent, an electrolyte magnesium salt, and an additive, wherein the additive is one or both of a sulfonyl imide additive or a phosphate additive, the sulfonyl imide additive is lithium bistrifluoromethanesulfonyl imide, the phosphate additive is trimethyl phosphate or triethyl phosphate, the concentration of the electrolyte magnesium salt in the electrolyte is 0.01-1.0M, the concentration of the sulfonyl imide additive in the electrolyte is 0.01-1.0M, and the total volume percentage of the phosphate additive in the electrolyte is 1%-50%.
[0006] Preferably, the concentration of the sulfonimide additive in the electrolyte is 0.1-0.6M, the molar ratio of the electrolyte magnesium salt to the sulfonimide additive is 1:0.5-4, and the total volume percentage of the phosphate additive in the electrolyte is 5%-10%.
[0007] Furthermore, the electrolyte magnesium salt is magnesium trifluoromethanesulfonate.
[0008] Furthermore, the organic ether solvent is at least one of tetrahydrofuran, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.
[0009] Furthermore, the electrolyte is dried by adding an appropriate amount of molecular sieve before use to make its water content less than 10 ppm. Molecular sieve.
[0010] The present invention provides a method for preparing the above-mentioned rechargeable magnesium battery composite electrolyte, comprising the following steps: in a glove box filled with argon atmosphere, adding electrolyte magnesium salt, sulfonimide additives and phosphate additives to an organic ether solvent, and fully heating and stirring to obtain the rechargeable magnesium battery composite electrolyte.
[0011] Furthermore, the oxygen content and moisture content of the glove box are both lower than 1 ppm; the organic ether solvent and phosphate additive are pre-dried by molecular sieve, and the molecular sieve is Molecular sieve; the heating and stirring conditions are: heating temperature is 40-90°C, stirring speed is 300-1000r / min.
[0012] The present invention provides the application of the above-mentioned rechargeable magnesium battery composite electrolyte in the fields of symmetrical batteries and asymmetrical batteries.
[0013] Furthermore, the symmetrical battery includes a positive electrode material, a negative electrode material, a diaphragm and a rechargeable magnesium battery composite electrolyte, wherein the positive electrode material is metallic magnesium or a magnesium alloy; the asymmetric battery includes a positive electrode material, a negative electrode material, a diaphragm and a rechargeable magnesium battery electrolyte, wherein the positive electrode material is aluminum, copper, molybdenum, stainless steel, titanium or zinc.
[0014] Furthermore, the negative electrode material is metal magnesium or a magnesium alloy, and the separator is at least one of a glass fiber separator, a polyethylene film, a polypropylene film or a polymer composite film.
[0015] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: lithium bis(trifluoromethanesulfonyl imide), trimethyl phosphate and triethyl phosphate can all improve the solubility of the electrolyte magnesium salt magnesium trifluoromethanesulfonate in ether solvents. By adding lithium bis(trifluoromethanesulfonyl imide), the diffusion kinetics of ions are significantly improved, and the solvation structure of the electrolyte can be effectively regulated to form a stable electrode / electrolyte interface, thereby improving the ionic conductivity, thereby achieving reversible electrochemical cycling of magnesium metal at high current density, and significantly improving the cycle stability of the battery. In addition, by introducing trimethyl phosphate or triethyl phosphate, a phosphorus-rich magnesium ion conductive interface film is formed on the surface of magnesium metal, enhancing the Mg 2+ The transfer capacity of magnesium anode is improved, the overpotential of magnesium dissolution / deposition is reduced, and the reversibility of magnesium deposition is improved, showing excellent electrochemical performance. The obtained electrolyte not only has excellent electrochemical performance, but also has a simple preparation process without complicated pretreatment and post-treatment steps, thereby greatly reducing the production cost. These advantages enable this technology to meet the requirements of commercialization of rechargeable magnesium batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The chronoamperometry diagram of the electrolyte prepared in Examples 1-6 and Comparative Example 1 at an overpotential of -0.5 V for 400 s for the Mg||Mg symmetric battery;
[0017] Figure 2LSV diagrams of the electrolytes prepared in Examples 1 to 7, Example 9 and Comparative Example 1 in asymmetric cells (Mg||Al, Mg||Cu, Mg||Mo, Mg||SS, Mg||Ti cells) composed of different research electrodes and magnesium electrodes;
[0018] Figure 3 The EIS graphs of the electrolytes prepared in Examples 1 to 6, Example 9 and Comparative Example 1 before and after cycling in a Mg||Mg symmetric battery;
[0019] Figure 4 The figure shows the charge and discharge curves of the electrolytes prepared in Example 4, Example 6-Example 12 and Comparative Example 1 in a Mg||Mg symmetrical battery. The test condition is a current density of 0.1 mA cm -2 , area capacity 0.05 mAh cm -2 ;
[0020] Figure 5 The charge and discharge curves of the electrolytes prepared in Examples 1 to 6 and 9 in a Mg||Mg symmetrical battery are shown in the figure. The test condition is a current density of 5 mA cm -2 , area capacity 2.5mAh cm -2 ;
[0021] Figure 6 The charge and discharge curves of the electrolytes prepared in Examples 1 to 6 in Mg||Mg symmetric cells, tested under a current density of 10 mA cm -2 , area capacity 1mAh cm -2 ;
[0022] Figure 7 The limiting current test diagram of the electrolyte prepared in Examples 1 to 6 in a Mg||Mg symmetric battery;
[0023] Figure 8 SEM images of the electrolytes prepared in Examples 1 to 6, Example 11 and Comparative Example 1 after magnesium metal dissolution / deposition electrochemical testing;
[0024] Fig. 9 XRD diagram of magnesium electrode after the electrolytes prepared in Examples 1 to 6, Example 11 and Comparative Example 1 were cycled in a Mg||Mg symmetric battery;
[0025] Fig.10 - (a) is a coulombic efficiency diagram of the electrolyte prepared in Example 4 in different asymmetric cells (Mg||Al, Mg||Cu, Mg||Mo, Mg||SS, Mg||Ti, Mg||Zn) and a coulombic efficiency diagram of the electrolyte prepared in Example 9 in a Mg||Al asymmetric cell; Fig.10- (b) is the charge and discharge curve of the electrolyte prepared in Example 9 in the Mg||Al asymmetric battery. DETAILED DESCRIPTION
[0026] The present invention is further described below in conjunction with specific embodiments and drawings.
[0027] Embodiment 1: The composite electrolyte for a rechargeable magnesium battery provided in this embodiment includes ethylene glycol dimethyl ether, magnesium trifluoromethanesulfonate and lithium bis(trifluoromethanesulfonyl)imide, wherein the concentration of magnesium trifluoromethanesulfonate in the electrolyte is 0.2M, and the concentration of lithium bis(trifluoromethanesulfonyl)imide in the electrolyte is 0.1M.
[0028] The preparation method of the above electrolyte is as follows: the electrolyte is prepared in a glove box filled with argon atmosphere, and the oxygen content and moisture content of the glove box are both less than 1ppm. Magnesium trifluoromethanesulfonate (Mg(OTf)2) and lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) are added to ethylene glycol dimethyl ether (DME) solvent to prepare 0.2M Mg(OTf)2+0.1M LiTFSI-DME electrolyte, and the target electrolyte is obtained after sufficient heating and stirring, the heating temperature is 60°C, and the stirring speed is 500r / min. The electrolyte is added with an appropriate amount of Molecular sieve drying. The moisture content of the electrolyte was tested to be less than 10ppm.
[0029] Embodiment 2: The composite electrolyte for a rechargeable magnesium battery provided in this embodiment includes ethylene glycol dimethyl ether, magnesium trifluoromethanesulfonate and lithium bis(trifluoromethanesulfonyl)imide, wherein the concentration of magnesium trifluoromethanesulfonate in the electrolyte is 0.2M, and the concentration of lithium bis(trifluoromethanesulfonyl)imide in the electrolyte is 0.2M.
[0030] The preparation method of the above electrolyte is as follows: the electrolyte is prepared in a glove box filled with argon atmosphere, and the oxygen content and moisture content of the glove box are both less than 1ppm. Magnesium trifluoromethanesulfonate (Mg(OTf)2) and lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) are added to ethylene glycol dimethyl ether (DME) solvent to prepare 0.2M Mg(OTf)2+0.2M LiTFSI-DME electrolyte, and the target electrolyte is obtained after sufficient heating and stirring, the heating temperature is 60°C, and the stirring speed is 500r / min. The electrolyte is added with an appropriate amount of Molecular sieve drying. The moisture content of the electrolyte was tested to be less than 10ppm.
[0031] Embodiment 3: The composite electrolyte for a rechargeable magnesium battery provided in this embodiment includes ethylene glycol dimethyl ether, magnesium trifluoromethanesulfonate and lithium bis(trifluoromethanesulfonyl)imide, wherein the concentration of magnesium trifluoromethanesulfonate in the electrolyte is 0.2M, and the concentration of lithium bis(trifluoromethanesulfonyl)imide in the electrolyte is 0.3M.
[0032] The preparation method of the above electrolyte is as follows: the electrolyte is prepared in a glove box filled with argon atmosphere, and the oxygen content and moisture content of the glove box are both less than 1ppm. Magnesium trifluoromethanesulfonate (Mg(OTf)2) and lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) are added to ethylene glycol dimethyl ether (DME) solvent to prepare 0.2M Mg(OTf)2+0.3M LiTFSI-DME electrolyte, and the target electrolyte is obtained after sufficient heating and stirring, the heating temperature is 60°C, and the stirring speed is 500r / min. The electrolyte is added with an appropriate amount of Molecular sieve drying. The moisture content of the electrolyte was tested to be less than 10ppm.
[0033] Embodiment 4: The composite electrolyte for a rechargeable magnesium battery provided in this embodiment includes ethylene glycol dimethyl ether, magnesium trifluoromethanesulfonate and lithium bis(trifluoromethanesulfonyl)imide, wherein the concentration of magnesium trifluoromethanesulfonate in the electrolyte is 0.2M, and the concentration of lithium bis(trifluoromethanesulfonyl)imide in the electrolyte is 0.4M.
[0034] The preparation method of the above electrolyte is as follows: the electrolyte is prepared in a glove box filled with argon atmosphere, and the oxygen content and moisture content of the glove box are both less than 1ppm. Magnesium trifluoromethanesulfonate (Mg(OTf)2) and lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) are added to ethylene glycol dimethyl ether (DME) solvent to prepare 0.2M Mg(OTf)2+0.4M LiTFSI-DME electrolyte, and the target electrolyte is obtained after sufficient heating and stirring, the heating temperature is 60°C, and the stirring speed is 500r / min. The electrolyte is added with an appropriate amount of Molecular sieve drying. The moisture content of the electrolyte was tested to be less than 10ppm.
[0035] Embodiment 5: The composite electrolyte for a rechargeable magnesium battery provided in this embodiment includes ethylene glycol dimethyl ether, magnesium trifluoromethanesulfonate and lithium bis(trifluoromethanesulfonyl)imide, wherein the concentration of magnesium trifluoromethanesulfonate in the electrolyte is 0.2M, and the concentration of lithium bis(trifluoromethanesulfonyl)imide in the electrolyte is 0.5M.
[0036] The preparation method of the above electrolyte is as follows: the electrolyte is prepared in a glove box filled with argon atmosphere, and the oxygen content and moisture content of the glove box are both less than 1ppm. Magnesium trifluoromethanesulfonate (Mg(OTf)2) and lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) are added to ethylene glycol dimethyl ether (DME) solvent to prepare 0.2M Mg(OTf)2+0.5M LiTFSI-DME electrolyte, and the target electrolyte is obtained after sufficient heating and stirring, the heating temperature is 60°C, and the stirring speed is 500r / min. The electrolyte is added with an appropriate amount of Molecular sieve drying. The moisture content of the electrolyte was tested to be less than 10ppm.
[0037] Embodiment 6: The composite electrolyte for a rechargeable magnesium battery provided in this embodiment includes ethylene glycol dimethyl ether, magnesium trifluoromethanesulfonate and lithium bis(trifluoromethanesulfonyl)imide, wherein the concentration of magnesium trifluoromethanesulfonate in the electrolyte is 0.2M, and the concentration of lithium bis(trifluoromethanesulfonyl)imide in the electrolyte is 0.6M.
[0038] The preparation method of the above electrolyte is as follows: the electrolyte is prepared in a glove box filled with argon atmosphere, and the oxygen content and moisture content of the glove box are both less than 1ppm. Magnesium trifluoromethanesulfonate (Mg(OTf)2) and lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) are added to ethylene glycol dimethyl ether (DME) solvent to prepare 0.2M Mg(OTf)2+0.6M LiTFSI-DME electrolyte, and the target electrolyte is obtained after sufficient heating and stirring, the heating temperature is 60°C, and the stirring speed is 500r / min. The electrolyte is added with an appropriate amount of Molecular sieve drying. The moisture content of the electrolyte was tested to be less than 10ppm.
[0039] Embodiment 7: The composite electrolyte for a rechargeable magnesium battery provided in this embodiment includes ethylene glycol dimethyl ether, magnesium trifluoromethanesulfonate and trimethyl phosphate, wherein the concentration of magnesium trifluoromethanesulfonate in the electrolyte is 0.1 M, and the volume fraction of trimethyl phosphate is 10%.
[0040] The preparation method of the above electrolyte solution is as follows: the electrolyte solution is prepared in a glove box filled with argon atmosphere, and the oxygen content and moisture content of the glove box are both less than 1ppm. Magnesium trifluoromethanesulfonate (Mg(OTf)2) and trimethyl phosphate (TMP) are added to ethylene glycol dimethyl ether (DME) solvent to prepare 0.1M Mg(OTf)2+10% (v / v) TMP-DME electrolyte solution, and the target electrolyte solution is obtained after sufficient heating and stirring, the heating temperature is 45°C, and the stirring speed is 500r / min. The electrolyte solution is added with an appropriate amount of Molecular sieve drying. The moisture content of the electrolyte was tested to be less than 10ppm.
[0041] Embodiment 8: The composite electrolyte for a rechargeable magnesium battery provided in this embodiment includes ethylene glycol dimethyl ether, magnesium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl imide) and trimethyl phosphate, wherein the concentration of magnesium trifluoromethanesulfonate in the electrolyte is 0.1 M, the concentration of lithium bis(trifluoromethanesulfonyl imide) in the electrolyte is 0.4 M, and the volume fraction of trimethyl phosphate is 10%.
[0042] The preparation method of the above electrolyte is as follows: the electrolyte is prepared in a glove box filled with argon atmosphere, and the oxygen content and moisture content of the glove box are both less than 1ppm. Magnesium trifluoromethanesulfonate (Mg(OTf)2), lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) and trimethyl phosphate (TMP) are added to ethylene glycol dimethyl ether (DME) solvent to prepare 0.1MMg(OTf)2+0.4MLiTFSI+10% (v / v) TMP-DME electrolyte, and the target electrolyte is obtained after sufficient heating and stirring, the heating temperature is 45°C, and the stirring speed is 500r / min. The electrolyte is added with an appropriate amount of Molecular sieve drying. The moisture content of the electrolyte was tested to be less than 10ppm.
[0043] Embodiment 9: The composite electrolyte for rechargeable magnesium battery provided in this embodiment includes ethylene glycol dimethyl ether, magnesium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl imide) and trimethyl phosphate, wherein the concentration of magnesium trifluoromethanesulfonate in the electrolyte is 0.2M, the concentration of lithium bis(trifluoromethanesulfonyl imide) in the electrolyte is 0.4M, and the volume fraction of trimethyl phosphate is 5%.
[0044] The preparation method of the above electrolyte is as follows: the electrolyte is prepared in a glove box filled with argon atmosphere, and the oxygen content and moisture content of the glove box are both less than 1ppm. Magnesium trifluoromethanesulfonate (Mg(OTf)2), lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) and trimethyl phosphate (TMP) are added to ethylene glycol dimethyl ether (DME) solvent to prepare 0.2MMg(OTf)2+0.4MLiTFSI+5% (v / v) TMP-DME electrolyte, and the target electrolyte is obtained after sufficient heating and stirring, the heating temperature is 45°C, and the stirring speed is 500r / min. The electrolyte is added with an appropriate amount of Molecular sieve drying. The moisture content of the electrolyte was tested to be less than 10ppm.
[0045] Embodiment 10: The composite electrolyte for rechargeable magnesium battery provided in this embodiment includes ethylene glycol dimethyl ether, magnesium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl imide) and trimethyl phosphate, wherein the concentration of magnesium trifluoromethanesulfonate in the electrolyte is 0.2M, the concentration of lithium bis(trifluoromethanesulfonyl imide) in the electrolyte is 0.4M, and the volume fraction of trimethyl phosphate is 7.5%.
[0046] The preparation method of the above electrolyte is as follows: the electrolyte is prepared in a glove box filled with argon atmosphere, and the oxygen content and moisture content of the glove box are both less than 1ppm. Magnesium trifluoromethanesulfonate (Mg(OTf)2), lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) and trimethyl phosphate (TMP) are added to ethylene glycol dimethyl ether (DME) solvent to prepare 0.2MMg(OTf)2+0.4MLiTFSI+7.5% (v / v) TMP-DME electrolyte, and the target electrolyte is obtained after sufficient heating and stirring, the heating temperature is 45°C, and the stirring speed is 500r / min. The electrolyte is added with an appropriate amount of Molecular sieve drying. The moisture content of the electrolyte was tested to be less than 10ppm.
[0047] Embodiment 11: The composite electrolyte for rechargeable magnesium battery provided in this embodiment includes ethylene glycol dimethyl ether, magnesium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl imide) and trimethyl phosphate, wherein the concentration of magnesium trifluoromethanesulfonate in the electrolyte is 0.2M, the concentration of lithium bis(trifluoromethanesulfonyl imide) in the electrolyte is 0.4M, and the volume fraction of trimethyl phosphate is 10%.
[0048] The preparation method of the above electrolyte is as follows: the electrolyte is prepared in a glove box filled with argon atmosphere, and the oxygen content and moisture content of the glove box are both less than 1ppm. Magnesium trifluoromethanesulfonate (Mg(OTf)2), lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) and trimethyl phosphate (TMP) are added to ethylene glycol dimethyl ether (DME) solvent to prepare 0.2MMg(OTf)2+0.4MLiTFSI+10% (v / v) TMP-DME electrolyte, and the target electrolyte is obtained after sufficient heating and stirring, the heating temperature is 45°C, and the stirring speed is 500r / min. The electrolyte is added with an appropriate amount of Molecular sieve drying. The moisture content of the electrolyte was tested to be less than 10ppm.
[0049] Example 12: The composite electrolyte for a rechargeable magnesium battery provided in this embodiment includes ethylene glycol dimethyl ether, magnesium trifluoromethanesulfonate, lithium bistrifluoromethanesulfonyl imide and triethyl phosphate, wherein the concentration of magnesium trifluoromethanesulfonate in the electrolyte is 0.2M, the concentration of lithium bistrifluoromethanesulfonyl imide in the electrolyte is 0.2M, and the volume fraction of triethyl phosphate is 10%.
[0050] The preparation method of the above electrolyte is as follows: the electrolyte is prepared in a glove box filled with argon atmosphere, and the oxygen content and moisture content of the glove box are both less than 1ppm. Magnesium trifluoromethanesulfonate (Mg(OTf)2), lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) and triethyl phosphate (TEP) are added to ethylene glycol dimethyl ether (DME) solvent to prepare 0.2M Mg(OTf)2+0.2MLiTFSI+10% (v / v)TEP-DME electrolyte, and the target electrolyte is obtained after sufficient heating and stirring, the heating temperature is 45°C, and the stirring speed is 500r / min. The electrolyte is added with an appropriate amount of Molecular sieve drying. The moisture content of the electrolyte was tested to be less than 10ppm.
[0051] Comparative Example 1: The electrolyte preparation method provided in this comparative example is as follows: the electrolyte is prepared in a glove box filled with argon atmosphere, and the oxygen content and moisture content of the glove box are both less than 1ppm. Magnesium trifluoromethanesulfonate (Mg(OTf)2) is added to ethylene glycol dimethyl ether (DME) solvent to prepare a 0.03M Mg(OTf)2-DME blank electrolyte, and the comparative electrolyte is obtained after sufficient heating and stirring. The heating temperature is 65°C and the stirring speed is 700r / min. The electrolyte is added with an appropriate amount of Molecular sieve drying. The moisture content of the electrolyte was tested to be less than 10ppm.
[0052] The electrolytes prepared in Examples 1 to 12 and Comparative Example 1 were subjected to performance tests. The battery performance tests were all conducted using a Blue Electric Battery Testing System and a Chenhua electrochemical workstation. The physical properties of the magnesium electrode surface after long cycles were characterized using a scanning electron microscope and an X-ray diffractometer. In order to test the electrochemical properties of the electrolyte, Mg||Mg symmetric batteries and asymmetric batteries (including Mg||Al, Mg||Cu, Mg||Mo, Mg||SS, Mg||Ti, Mg||Zn) were used respectively. The electrolytes prepared in the above examples were used, and the diaphragm was glass fiber. They were assembled into CR2032 button batteries, and magnesium metal dissolution / deposition, electrochemical impedance spectroscopy, linear sweep voltammetry, chronoamperometry, asymmetric battery charge and discharge and other tests were conducted. In order to characterize the morphological structure and material composition of the electrode surface after cycling, the battery pole pieces after long cycles were subjected to SEM and XRD test analysis. The test results are shown in the table below. Figure 1-Figure 10 .
[0053] Figure 1 The chronoamperometry diagrams of the electrolytes prepared in Examples 1-6 and Comparative Example 1 for the Mg||Mg symmetric cell at -0.5V overpotential within 400s are shown. The test results show that the current of the electrolytes prepared in Examples 1-6 quickly reaches a steady state during the electrochemical reaction, indicating that the electrolyte composed of an organic ether solvent, an electrolyte magnesium salt, and a sulfonimide additive exhibits a stable three-dimensional diffusion pattern.
[0054] Figure 2 LSV diagrams of the electrolytes prepared in Examples 1 to 7, Example 9 and Comparative Example 1 in asymmetric cells (Mg||Al, Mg||Cu, Mg||Mo, Mg||SS, Mg||Ti cells) with different research electrodes and magnesium electrodes. The test conditions were a voltage range from OCV to 6.5V and a scan rate of 5mV s -1 The test results show that after adding 0.1-0.5M LiTFSI, when Cu is used as the research electrode, the electrochemical window of the electrolyte only reaches 2.0V, and when Al, Mo, SS, and Ti are used as the research electrodes, the electrochemical window of the electrolyte reaches above 4.0V, indicating that this type of electrolyte has a wide electrochemical window and high oxidation stability. In addition, when LiTFSI and TMP are added at the same time, the electrolyte also has a wide electrochemical window.
[0055] Figure 3 The EIS graphs of the electrolytes prepared in Examples 1 to 6, Example 9 and Comparative Example 1 before and after cycling in a Mg||Mg symmetric battery. The test results show that adding LiTFSI to the electrolyte, or adding LiTFSI and TMP at the same time, can significantly reduce the charge transfer resistance. However, the impedance caused by ion diffusion limitation is still high.
[0056] Figure 4 The figure shows the charge and discharge curves of the electrolytes prepared in Example 4, Example 6-Example 12 and Comparative Example 1 in a Mg||Mg symmetrical battery. The test condition is a current density of 0.1 mA cm -2 , area capacity 0.05 mAh cm -2 . The test results show that in the Mg(OTf)2-DME blank electrolyte, the dissolution / deposition overpotential of magnesium metal is high and the stability is poor; when LiTFSI or TMP is added to the electrolyte, the dissolution / deposition overpotential of magnesium metal is significantly reduced, and the cycle stability is improved. Furthermore, when LiTFSI and TMP are added together, the synergistic effect of the two improves the charge and discharge performance and cycle stability of magnesium metal in the Mg||Mg symmetric battery. Although the simultaneous addition of LiTFSI and TEP helps to reduce the dissolution / deposition overpotential of magnesium metal, under this condition, the cycle stability of the battery still needs to be further improved.
[0057] Figure 5 The charge and discharge curves of the electrolytes prepared in Examples 1 to 6 and 9 in a Mg||Mg symmetrical battery are shown in the figure. The test condition is a current density of 5 mA cm -2 , area capacity 2.5mAh cm -2. The test results show that the addition of LiTFSI greatly promotes the interfacial charge transfer kinetics, which can achieve long charge and discharge cycles of the magnesium metal negative electrode at high current density. When the concentration of LiTFSI reaches 0.2M, the battery can achieve a stable charge and discharge cycle of more than 2000 hours, and the dissolution / deposition overpotential of magnesium metal is only 0.4V, showing excellent electrochemical performance. In addition, the simultaneous addition of LiTFSI and TMP can also promote the charge and discharge cycle performance of the magnesium metal negative electrode at high current density.
[0058] Figure 6 The charge and discharge curves of the electrolytes prepared in Examples 1 to 6 in Mg||Mg symmetric cells, tested under a current density of 10 mA cm -2 , area capacity 1mAh cm -2 The test results show the effect of different concentrations of LiTFSI on the battery charge and discharge performance under high current conditions. When the concentration of LiTFSI exceeds 0.5M, the battery's cycle stability will decrease significantly.
[0059] Figure 7 The limiting current test diagram of the electrolyte prepared in Examples 1 to 6 in a Mg||Mg symmetric battery. The current density test range is 5-60 mA cm -2 (The increase is 5mA cm -2 ), the battery was activated before the test. During the test, the battery was charged and discharged 10 times at different current densities, with each cycle lasting 6 minutes. -2 The long-cycle charge-discharge test was carried out at a current density of Figure 7 As shown in (a)-(f), when 0.1-0.3 M LiTFSI is added to the electrolyte, the -2 ), the symmetrical battery can still maintain a stable potential curve during the deposition and dissolution of magnesium, especially when 0.2MLiTFSI is added, the overpotential is maintained below 0.8V. This shows that this type of electrolyte has the characteristics of withstanding ultra-large currents.
[0060] Figure 8 The SEM images of the electrolytes prepared in Examples 1 to 6, Example 11 and Comparative Example 1 after the magnesium metal dissolution / deposition electrochemical test. The test results show that after the charge and discharge cycle of the Mg||Mg symmetric battery using the Mg(OTf)2-DME blank electrolyte, the magnesium electrode surface is smooth (e.g. Figure 8 -(a)). In contrast, after the charge-discharge cycle of the Mg||Mg symmetric battery containing LiTFSI electrolyte, dense deposits (such as Figure 8 In addition, when LiTFSI and TMP are added to the electrolyte at the same time, the Mg||Mg symmetric battery also shows dense deposits on the magnesium electrode surface after charge and discharge cycles (such as Figure 8 -(h)).
[0061] Fig. 9 XRD patterns of magnesium electrodes after the electrolytes prepared in Examples 1 to 6, Example 11 and Comparative Example 1 were cycled in a Mg||Mg symmetric battery. The test results show that the magnesium metal negative electrode deposit is mainly composed of elemental magnesium, and the characteristic peaks of the XRD image after battery cycling correspond to the magnesium metal PDF card. The surface phase of the magnesium electrode has no obvious change, and has high reversibility.
[0062] Fig.10 - (a) is a coulombic efficiency diagram of the electrolyte prepared in Example 4 in different asymmetric cells (Mg||Al, Mg||Cu, Mg||Mo, Mg||SS, Mg||Ti, Mg||Zn) and a coulombic efficiency diagram of the electrolyte prepared in Example 9 in a Mg||Al asymmetric cell; Fig.10 - (b) is the charge-discharge curve of the electrolyte prepared in Example 9 in the Mg||Al asymmetric battery. The test condition is a current density of 0.5 mA cm -2 , area capacity 0.25 mAh cm -2 The test results show that when 0.4M LiTFSI is added, the average coulombic efficiency of the asymmetric battery is low, among which the coulombic efficiency of the Mg||Zn asymmetric battery is only 60%. On this basis, after adding 5% TMP, its coulombic efficiency is significantly improved. After 50 cycles, the coulombic efficiency of the Mg||Al asymmetric battery can reach 91.60%. This shows that the addition of TMP can significantly improve the cyclic reversibility of the battery.
Claims
1. A composite electrolyte for a rechargeable magnesium battery, characterized in that: The electrolyte comprises an organic ether solvent, an electrolyte magnesium salt, and an additive, wherein the additive is one or both of a sulfonyl imide additive and a phosphate ester additive, the concentration of the electrolyte magnesium salt in the electrolyte is 0.01-1.0 M, the concentration of the sulfonyl imide additive in the electrolyte is 0.01-1.0 M, and the total volume percentage of the phosphate ester additive in the electrolyte is 1%-50%.
2. The rechargeable magnesium battery composite electrolyte according to claim 1, characterized in that: The sulfonyl imide additive is at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, sodium bis(trifluoromethanesulfonyl)imide, magnesium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-propylpiperidinium bis(trifluoromethanesulfonyl)imide salt, and 1-butyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide salt.
3. The rechargeable magnesium battery composite electrolyte according to claim 1, characterized in that: The phosphate additive is at least one of trimethyl phosphate, triethyl phosphate and tripropyl phosphate.
4. The composite electrolyte for rechargeable magnesium batteries according to any one of claims 1 to 3, characterized in that: The concentration of the sulfonyl imide additive in the electrolyte is 0.1-0.6M, the molar ratio of the electrolyte magnesium salt to the sulfonyl imide additive is 1:0.5-4, and the total volume percentage of the phosphate additive in the electrolyte is 5%-10%.
5. The rechargeable magnesium battery composite electrolyte according to claim 1, characterized in that: The electrolyte magnesium salt is magnesium trifluoromethanesulfonate.
6. The composite electrolyte for rechargeable magnesium batteries according to claim 1, characterized in that: The organic ether solvent is at least one of tetrahydrofuran, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.
7. A method for preparing a composite electrolyte for a rechargeable magnesium battery according to any one of claims 1 to 6, characterized in that: The following steps are involved: In a glove box filled with argon atmosphere, electrolyte magnesium salt, sulfonimide additives and phosphate additives are added to an organic ether solvent in sequence, and a rechargeable magnesium battery composite electrolyte is obtained after sufficient heating and stirring.
8. The preparation method according to claim 7, characterized in that: The oxygen content and moisture content of the glove box are both lower than 1 ppm; the organic ether solvent and phosphate additive are pre-dried with molecular sieves; the heating and stirring conditions are: the heating temperature is 40-90° C., and the stirring speed is 300-1000 r / min.
9. Use of the composite electrolyte for rechargeable magnesium batteries according to any one of claims 1 to 6 in the fields of symmetrical batteries and asymmetrical batteries.
10. The use according to claim 9, characterized in that: The symmetrical battery comprises a positive electrode material, a negative electrode material, a diaphragm and a composite electrolyte for a rechargeable magnesium battery, wherein the positive electrode material is metal magnesium or a magnesium alloy; the asymmetric battery comprises a positive electrode material, a negative electrode material, a diaphragm and a composite electrolyte for a rechargeable magnesium battery, wherein the positive electrode material is aluminum, copper, molybdenum, stainless steel, titanium or zinc, the negative electrode material is metal magnesium or a magnesium alloy, and the diaphragm is at least one of a glass fiber diaphragm, a polyethylene film, a polypropylene film or a polymer composite film.
Citation Information
Cited By
Magnesium-lithium composite electrolyte of rechargeable magnesium battery as well as preparation method and application of magnesium-lithium composite electrolyte
CN119419360A
Magnesium secondary battery electrolyte and preparation method thereof
CN120767411A
Non-aqueous electrolyte of dianion salt magnesium fuel cell
CN121484146A